Transition from socialist to market economies : comparison of European and Asian experiences - Ichimura, Shinʼichi, 1925-; Sato, Tsuneaki, 1925-; James, William E. (Houndmills : Palgrave MacMillan, 2009)
'20 years after the collapse of communism in Central Eastern European countries and 30 years after the start of market-oriented reforms in China, this book provides a framework for understanding the differing emphasis and sequencing of two reforms and explores in-depth these issues in the demise of communism and the triumph of the market economy'--Provided by publisher.
Includes bibliographical references and indexes.
Keywords: Mixed economy -- Europe, Eastern; Post-communism -- Europe, Eastern; Mixed economy -- China; Europe, Eastern -- Economic conditions -- 1989-; China -- Economic conditions -- 1976-2000.